2021
DOI: 10.1155/2021/7259496
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Mucoepidermoid Carcinoma Mimicking Deteriorated Bronchial Asthma during Pregnancy

Abstract: Primary bronchial tumors are extremely rare. However, symptoms, such as coughing and wheezing, are not specific to this disease, and primary bronchial tumors are often misdiagnosed as bronchial asthma. This report describes the case of a pregnant patient with a bronchial tumor that mimicked deteriorating bronchial asthma. A 37-year-old female patient suffered from repeated episodes of pneumonia since 26 weeks of gestation. Despite treatment, she suffered from another episode of pneumonia at 28 weeks of gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…MSCT imaging had a good practical value in the clinical diagnosis of primary tracheal tumors in cardiothoracic surgery, which was consistent with the research results of Tran et al. (2019) ( 32 ). In the study by Li et al., it was found that the use of MSCT could significantly identify the shape and density of duodenal adenomatous nodules, thereby improving the detection rate of tumors ( 32 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…MSCT imaging had a good practical value in the clinical diagnosis of primary tracheal tumors in cardiothoracic surgery, which was consistent with the research results of Tran et al. (2019) ( 32 ). In the study by Li et al., it was found that the use of MSCT could significantly identify the shape and density of duodenal adenomatous nodules, thereby improving the detection rate of tumors ( 32 ).…”
Section: Discussionsupporting
confidence: 89%
“…The diagnostic accuracy of patients' MSCT images reflected that, compared with original CT images, the diagnostic accuracy of the VR, MPVR, and CTVE images in tumor morphology, the extent of the long-axis involvement of the duct wall, and the degree of wall stenosis was obviously improved, with significant differences (P<0.05). MSCT imaging had a good practical value in the clinical diagnosis of primary tracheal tumors in cardiothoracic surgery, which was consistent with the research results of Tran et al (2019) (32). In the study by Li et al, it was found that the use of MSCT could significantly identify the shape and density of duodenal adenomatous nodules, thereby improving the detection rate of tumors (32).…”
Section: Discussionsupporting
confidence: 80%
“…Tracheal tumors present with non-specific symptoms, such as cough, wheezing, and shortness of breath (1). These clinical presentations of tracheal tumors sometimes lead to a misdiagnosis as asthma (2)(3)(4)(5)(6), but tracheal tumors complicated with asthma are rare. The common pathology of tracheal tumors is squamous cell and adenoid cystic carcinoma (7), and tracheal glomus tumors are infrequent (8).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review (13) showed that most common symptoms of tracheal glomus tumors were consistent with those of wholetracheal tumors: dyspnea (55%), cough (55%), and hemoptysis (44%). Clinical presentations, except for hemoptysis, may lead to a misdiagnosis of asthma (2)(3)(4)(5)(6). In fact, these mimicking symptoms often lead to a delay in the diagnosis, with the time lag sometimes spanning several years (3,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation